Salient object detection: a mini review - Wang, Xiuwenxin; Yu, Siyue; Lim, Eng Gee; Wong, M. L. Dennis (Frontiers in Signal Processing, 2024)
This paper presents a mini-review of recent works in Salient Object Detection (SOD). First, We introduce SOD and its application in image processing tasks and applications. Following this, we discuss the conventional methods for SOD and present several recent works in this category. With the start of deep learning AI algorithms, SOD has also benefited from deep learning. Here, we present and discuss Deep learning-based SOD according to its training mechanism, i.e. fully supervised and weakly supervised. For the benefit of the readers, we have also included some standard data sets assembled for SOD research.